Biomass hard carbon negative electrode material and preparation method and application thereof

Through the appropriate concentration of organic acid pretreatment and subsequent carbonization treatment, high-performance biomass hard carbon anode material was prepared, which solved the problem of low sodium storage capacity in traditional sodium ion batteries, and achieved the efficient electrochemical performance of sodium ion batteries and Simple process, suitable for large-scale applications.

CN119118100AActive Publication Date: 2024-12-13JIANGMEN DUAL CARBON LAB

Patent Information

Application Number
CN202411232088.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The traditional graphite negative electrode has low sodium storage capacity in existing sodium ion batteries, which is difficult to meet the needs of large-scale production, and the preparation process of biomass-derived hard carbon materials is complex, making it difficult to achieve commercial application.

Method used

Pretreatment of organic acids at an appropriate concentration is used to remove hemicellulose, retain cellulose and lignin, and prepare biomass hard carbon anode material through pre-carbonization, alkali treatment and acid treatment steps to optimize its electrochemical properties.

Benefits of technology

It significantly improves the electrochemical performance of biomass hard carbon anode material in sodium ion batteries, including improving the initial discharge capacity and the first Coulomb efficiency, and has a simple process and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118100A_ABST
    Figure CN119118100A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass hard carbon negative electrode material and a preparation method and application thereof. According to the method, the waste biomass is used as a raw material, selective dissolution regulation of hemicellulose in plants is realized only through pretreatment of the organic acid with proper concentration under the condition of not damaging natural structures of the plants, and cellulose and lignin components are reserved; the biomass hard carbon negative electrode material with improved performance can be obtained through two-step carbonization and acid-base treatment, so that the assembled sodium ion battery has excellent electrochemical performance, and under the condition that the current density is 50mA / g, the first discharge capacity is 286-345mAh / g, the first coulombic efficiency is 92-95%, and the cycle capacity is stable. The method can be used as a universal strategy for optimizing the electrochemical performance of the biomass hard carbon, the preparation process is low in cost and simple, and large-scale application and production of high-performance sodium ion batteries are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery energy storage, and specifically relates to a biomass hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Due to the global climate change problem caused by the widespread use of fossil fuels, humans have made great efforts to find new energy storage and utilization technologies. Among the existing and efficient energy storage devices, secondary batteries are considered to be high-energy density storage systems, which are ideal for portable electronic devices, hybrid vehicles and large industrial equipment. Lithium-ion batteries currently occupy the main market for secondary batteries, but due to limited lithium mineral resources, the price of lithium battery materials represented by lithium carbonate fluctuates greatly with the market. Compared with lithium, sodium resources have the advantages of abundant reserves, wide distribution and low price, and are expected to be used for large-scale energy storage.

[0003] In sodium-ion batteries, negative electrode materials play an important role in storing sodium ions. Traditional graphite negative electrodes are difficult to be used in sodium-ion batteries due to their low sodium storage capacity. Hard carbon materials are also difficult to graphitize above 2500°C. There are more pores inside them and larger interlayer spacing, so that sodium ions with larger ionic radius can also be freely deintercalated and have higher sodium storage capacity. Hard carbon materials are widely available and low in cost, especially hard carbon derived from biomass materials, which is often renewable and has attracted the attention of researchers. At present, reports on biomass-derived hard carbon materials mainly include lantern fruit shells, walnut shells, peanut shells, straw, etc. However, the sodium-ion batteries prepared from biomass-derived hard carbon materials currently need to go through complex hard carbon material preparation processes (such as complex pretreatment processes, organic coating and doping processes) to improve the performance of the prepared sodium-ion batteries, which is difficult to meet the requirements of commercial sodium-ion battery material negative electrodes for large-scale production. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects and shortcomings in the prior art and to provide a method for preparing a biomass hard carbon negative electrode material.

[0005] The second object of the present invention is to provide a biomass hard carbon negative electrode material prepared by the preparation method.

[0006] The third object of the present invention is to provide an application of the biomass hard carbon negative electrode material in the preparation of a sodium ion battery.

[0007] A fourth object of the present invention is to provide a sodium ion battery.

[0008] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0009] The present invention first provides a method for preparing a biomass hard carbon negative electrode material, comprising the following steps:

[0010] S1. The waste biomass is crushed and sieved, pretreated with 10-50wt% organic acid solution to selectively remove hemicellulose and retain cellulose and lignin, washed and dried to obtain a biomass hard carbon precursor;

[0011] S2. The biomass hard carbon precursor obtained in step S1 is pre-carbonized under an inert atmosphere to obtain a preliminary biomass hard carbon material;

[0012] S3. The preliminary biomass hard carbon material obtained in step S2 is sequentially subjected to alkali treatment and acid treatment, washed to neutrality, dried, and carbonized under an inert atmosphere to obtain a sodium ion battery hard carbon negative electrode material.

[0013] Wherein, the organic acid solution is a solution prepared by diluting the corresponding organic acid with deionized water, and the wt% is w / w.

[0014] Biomass materials mainly include cellulose, hemicellulose, and lignin components. The present invention selectively removes hemicellulose from different waste biomasses and retains cellulose and lignin through organic acid pretreatment with an appropriate concentration. While retaining the natural structure of the biomass, the hemicellulose is removed as much as possible and cellulose and lignin are retained. The results show that after retaining cellulose and lignin and removing hemicellulose, the electrochemical performance can be significantly improved, thereby achieving the optimization and regulation of the sodium storage performance of biomass hard carbon negative electrode materials. Compared with inorganic acid pretreatment or no organic acid pretreatment, the performance of sodium ion batteries assembled with biomass hard carbon negative electrode materials prepared by organic acid pretreatment is improved, especially the initial discharge capacity and the first coulombic efficiency are significantly improved, and the specific capacity is high and the cycle stability is good. However, after a higher concentration of organic acid pretreatment, the cellulose in the biomass is retained, but more lignin is removed. The performance improvement effect of the sodium ion battery assembled with the biomass hard carbon negative electrode material prepared by the organic acid pretreatment is worse than that of the lower concentration of organic acid pretreatment. Furthermore, regulating the biomass components (selectively removing and retaining cellulose and lignin) through organic acid pretreatment to improve the electrochemical performance (capacity, first-cycle coulomb efficiency) is a universal and effective means, which is suitable for optimizing the performance of hard carbon materials prepared from different biomasses. Although plant precursors have their own morphological distributions, they are affected by their growth environment. Different precursors have different proportions of cellulose, hemicellulose, and lignin components in the biomass, different distribution morphologies, and different element proportions; after carbonization, the pore structure and distribution are different, and the interlayer spacing is different, which ultimately leads to capacity differences. Although different biomasses exhibit different performances, the selective removal of hemicellulose by organic acid pretreatment can improve the electrochemical performance of biomass, but the improvement effect is different. The results of the present invention show that the selective regulation of hemicellulose by organic acid pretreatment at an appropriate concentration can be used as a universal strategy for optimizing the electrochemical properties of biomass hard carbon.

[0015] Furthermore, the waste biomass is selected from one or more of fan palm, straw, and banana peel.

[0016] Preferably, the waste biomass is Livistona chinensis, and the first coulombic efficiency of a sodium ion battery assembled with the Livistona chinensis-based hard carbon negative electrode material prepared in the present invention can be as high as 94.7%.

[0017] Further preferably, the fan palm is selected from one or more of the fan palm stems, fan palm leaves and fan palm roots.

[0018] More preferably, the palmetto is a palmetto stem.

[0019] Furthermore, the biomass in step S1 is washed and dried before being crushed and screened; the drying temperature is 60-120° C., the drying time is 6-24 hours, preferably dried at 80° C. for 12 hours.

[0020] Furthermore, the sieving specification is: 40-100 mesh, preferably 60 mesh.

[0021] Furthermore, the organic acid includes but is not limited to acetic acid, formic acid, glycolic acid or pyruvic acid.

[0022] Preferably, the organic acid is formic acid.

[0023] Furthermore, the concentration of the organic acid solution in step S1 is 10 wt % to 30 wt %.

[0024] Preferably, the organic acid solution in step S1 is 10 wt %.

[0025] Furthermore, in step S1, the pretreatment temperature of the organic acid solution is 30-100° C., the treatment time is 0.5-5 h, and the solid-liquid ratio (g / mL) is 1:3-10.

[0026] Preferably, in step S1, the pretreatment temperature of the organic acid solution is 60° C., the time is 1 h, and the solid-liquid ratio (g / mL) is 1:8.

[0027] Furthermore, the pre-carbonization treatment in step S2 is calcination at 400-800° C. for 1-5 hours.

[0028] Furthermore, the heating rate of the pre-carbonization treatment is 1-10°C / min.

[0029] Preferably, the inert atmosphere is argon or helium, preferably argon.

[0030] Preferably, the pre-carbonization treatment is calcination at 400-700° C. for 3 hours.

[0031] Preferably, the heating rate of the pre-carbonization treatment is 3-5°C / min.

[0032] Furthermore, in the alkali treatment in step S3, the alkali concentration is 2 to 15 wt %, and the alkali treatment time is 1 to 5 h.

[0033] Preferably, the alkaline solution used in the alkaline treatment in step S3 is potassium hydroxide or sodium hydroxide.

[0034] Further preferably, the alkali treatment in step S3 is soaking in 10 wt % sodium hydroxide solution for 1 hour.

[0035] Furthermore, in the acid treatment in step S3, the acid concentration is 0.5 to 6 mol / L, and the acid treatment time is 1 to 5 hours.

[0036] Preferably, the acid solution in the acid treatment in step S3 is any one of hydrochloric acid, nitric acid or sulfuric acid.

[0037] Further preferably, the acid treatment in step S3 is immersion in a 1 mol / L nitric acid solution for 0.5 h.

[0038] Preferably, in step S3, the preliminary biomass hard carbon material is subjected to alkali treatment and acid treatment, and then needs to be cleaned and dried before being subjected to a second calcination, i.e., carbonization treatment.

[0039] Preferably, the drying temperature is 60-120° C., and the drying time is 6-24 h; more preferably, the drying is performed at 80° C. for 12 h.

[0040] Furthermore, the carbonization treatment in step S3 is calcination at 1000-1500° C. for 1-6 hours.

[0041] Furthermore, the carbonization treatment heating rate is 2-5°C / min.

[0042] Preferably, the carbonization treatment is performed by heating the temperature to 1400° C. at 3° C. / min and calcining for 2 hours.

[0043] The present invention also provides a biomass hard carbon negative electrode material prepared by any of the above methods.

[0044] The present invention also provides the use of the biomass hard carbon negative electrode material in preparing a sodium ion battery.

[0045] The present invention also provides a sodium ion battery, comprising a negative electrode material, wherein the active material of the negative electrode material is the above-mentioned biomass hard carbon negative electrode material.

[0046] Furthermore, in the sodium ion battery, the negative electrode is prepared by grinding the above-mentioned biomass hard carbon negative electrode material and the adhesive sodium carboxymethyl cellulose in a mass ratio of 9:1, uniformly mixing them with deionized water as a solvent and coating them on a copper foil, and vacuum drying them at 80°C for 12 hours.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) The present invention uses waste biomass as raw material and adopts organic acid pretreatment of appropriate concentration to achieve selective dissolution and regulation of hemicellulose in plants while retaining cellulose and lignin components without destroying the natural structure of plants. It can improve the electrochemical properties of biomass hard carbon negative electrode materials, thereby achieving optimized regulation of the sodium storage performance of biomass hard carbon negative electrode materials, so that the biomass hard carbon negative electrode materials present more excellent electrochemical performance in the assembled sodium ion battery.

[0049] (2) The method for preparing the biomass hard carbon negative electrode of the present invention is simple. The composition of the plant components of the biomass is regulated by the preliminary organic acid pretreatment, and then the biomass hard carbon negative electrode material with improved performance can be obtained through two steps of carbonization and acid-base treatment, so that the assembled sodium ion battery has excellent electrochemical performance and higher first-cycle coulomb efficiency. The selective regulation of hemicellulose by the organic acid pretreatment with an appropriate concentration of the present invention can be used as a universal strategy for optimizing the electrochemical properties of biomass hard carbon, and the preparation process is low-cost and simple, which is conducive to the large-scale application of high-performance sodium ion batteries.

[0050] (3) The sodium ion battery prepared based on the biomass hard carbon negative electrode material of the present invention has an initial discharge capacity of 286-346 mAh / g and an initial coulombic efficiency of 92-95% at a current density of 50 mA / g, and a stable cycle capacity. Among them, the sodium ion battery prepared using the palmetto-based hard carbon negative electrode material has a maximum initial discharge capacity of 345.2 mAh / g, an initial coulombic efficiency of 94.7%, and a stable cycle capacity, indicating that the biomass hard carbon negative electrode material of the present invention has good prospects in the industrial application of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a graph showing the first charge and discharge capacity of the biomass hard carbon negative electrode material for sodium ion battery prepared in Example 1.

[0052] Figure 2 The charge and discharge capacity and coulomb efficiency curve of the biomass hard carbon negative electrode material for sodium ion battery prepared in Example 1.

[0053] Figure 3 1 is the XRD diagram of the biomass hard carbon negative electrode material prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0054] Figure 4 It is a comparison chart of the charge and discharge curves of the biomass hard carbon negative electrode material treated with inorganic acid in Example 1 and Comparative Examples 4 and 5. DETAILED DESCRIPTION

[0055] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0056] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0057] Example 1

[0058] A method for preparing a palm-based hard carbon negative electrode material comprises the following steps:

[0059] (1) 5 g of palmetto stems were cleaned with purified water, vacuum dried, crushed, sieved through a 60-mesh sieve, and then treated with 40 mL of a 10 wt % organic acid solution at a temperature of 60 ° C for 1 h; washed with deionized water and dried to obtain a biomass hard carbon material precursor; the organic acid was formic acid;

[0060] (2) placing the precursor material obtained in step (1) in a tubular furnace for pre-carbonization, and calcining it at a temperature of 3°C / min from room temperature to 600°C for 3 h in an argon atmosphere to obtain a preliminary biomass hard carbon material;

[0061] (3) placing the preliminary biomass hard carbon material obtained in step (2) in a 10 wt% NaOH solution and stirring for 1 hour;

[0062] (4) adding 6 mol / L nitric acid solution to the solution obtained in step (3), washing with deionized water until neutral, filtering and transferring to a vacuum oven at 80° C. for further drying for 12 h;

[0063] (5) The dried biomass hard carbon material obtained in step (4) is placed in a tubular furnace and calcined at a temperature of 3°C / min from room temperature to 1400°C for 2 h in an argon atmosphere to obtain a biomass hard carbon negative electrode material for a sodium ion battery.

[0064] Example 2

[0065] The difference between this embodiment and embodiment 1 is that the concentration of the organic acid solution in step (1) is 30 wt %.

[0066] Example 3

[0067] The difference between this embodiment and embodiment 1 is that the concentration of the organic acid solution in step (1) is 50 wt %.

[0068] Example 4

[0069] The difference between this embodiment and embodiment 1 is that the biomass raw material is waste banana peels.

[0070] Example 5

[0071] The difference between this embodiment and embodiment 1 is that the biomass raw material is waste straw.

[0072] Example 6

[0073] The difference between this embodiment and embodiment 1 is that the concentration of the organic acid solution in step (1) is 30 wt %, the material-liquid ratio is 1:9, the pre-carbonization temperature is 700° C., and the concentration of the acid solution after pre-carbonization is 6 mol / L hydrochloric acid.

[0074] Example 7

[0075] The difference between this embodiment and embodiment 1 is that the concentration of the organic acid solution in step (1) is 80 wt %, the material-liquid ratio is 1:7, and the concentration of the alkaline solution after pre-carbonization is 12 wt % NaOH.

[0076] Example 8

[0077] The difference between this embodiment and embodiment 1 is that the organic acid in step (1) is pyruvic acid with a concentration of 10 wt %, a material-liquid ratio of 1:8, and the concentration of the alkaline solution after pre-carbonization is 12 wt % NaOH.

[0078] Example 9

[0079] The difference between this embodiment and embodiment 1 is that the organic acid in step (1) is pyruvic acid, the concentration is 30 wt %, the material-liquid ratio is 1:10, and the pre-carbonization temperature is 500° C.

[0080] Comparative Example 1

[0081] The difference between this comparative example and Example 1 is that the biomass raw material, the palm leaves, are crushed and sieved, and then directly placed into a carbonization furnace without any treatment and carbonized at 1300° C. for 2 hours in a nitrogen atmosphere to obtain a hard carbon material.

[0082] Comparative Example 2

[0083] The difference between this comparative example and Example 1 is that in step (1), the biomass raw material, the palm stems, are not treated with organic acid.

[0084] Comparative Example 3

[0085] The difference between this comparative example and Example 1 is that the concentration of the organic acid solution in step (1) is 80 wt %.

[0086] Comparative Example 4

[0087] The difference between this comparative example and Example 1 is that in step (1), the biomass raw material, the palmetto stems, are treated with an inorganic acid, wherein the inorganic acid is hydrochloric acid with a concentration of 30 wt%.

[0088] Comparative Example 5

[0089] The difference between this comparative example and Example 1 is that in step (1), the biomass raw material, the palmetto stems, are treated with an inorganic acid, wherein the inorganic acid is sulfuric acid with a concentration of 20 wt%.

[0090] Comparative Example 6

[0091] The difference between this comparative example and Example 4 is that in step (1), the biomass raw material banana peel is not treated with organic acid.

[0092] Comparative Example 7

[0093] The difference between this comparative example and Example 5 is that in step (1), the biomass raw material straw is not treated with organic acid.

[0094] Test Case

[0095] The plant components of the biomass pretreated with organic acid in Examples 1 to 5 and pretreated in different ways in Comparative Examples 1 to 7 were determined, and the content of cellulose, hemicellulose and lignin in the plant components was determined by the NREL method. The results are shown in Table 1. In addition, the sodium ion batteries assembled in Examples 1 to 5 and Comparative Examples 1 to 7 were tested for electrochemical performance. The sodium ion battery is prepared by uniformly mixing the hard carbon negative electrode material with the binder (sodium carboxymethyl cellulose) in a mass ratio of 9:1 through a small ball mill, and then adding an appropriate amount of deionized water to uniformly mix to obtain an electrode slurry; the electrode slurry is coated on the current collector, and the battery negative electrode sheet is obtained by stamping after vacuum drying. The prepared battery negative electrode sheet is assembled into a sodium ion battery with metallic sodium, glass fiber diaphragm, electrolyte, battery shell, gasket, shrapnel, etc. The test conditions are a current density of 50mA / g and a voltage range of 0 to 3V. The test results are shown in Table 2.

[0096] Table 1 Mass of the three major components of biomass after pretreatment in Examples 1 to 5 and Comparative Examples 1 to 7

[0097]

[0098]

[0099] Table 2 Electrochemical performance of sodium ion batteries assembled from Examples 1 to 5 and Comparative Examples 1 to 7

[0100]

[0101] According to Table 1, compared with the untreated biomass (Comparative Examples 1-2, 6-7), after organic acid pretreatment, the mass of hemicellulose in the biomass was greatly reduced, while the mass of cellulose and lignin remained unchanged or slightly reduced, and after high concentration organic acid pretreatment (Comparative Example 3) and inorganic acid pretreatment (Comparative Examples 4, 5), the mass of hemicellulose and lignin in the biomass decreased significantly. Therefore, the results show that the appropriate concentration of organic acid pretreatment can selectively remove hemicellulose from different waste biomasses and retain cellulose and lignin, while inorganic acid and excessively high concentration of organic acid treatment cannot.

[0102] According to Table 2, the sodium ion battery assembled with the hard carbon negative electrode prepared in Examples 1 to 5 has excellent battery performance, with an initial discharge capacity of 286 to 346 mAh / g, a first coulombic efficiency of 92 to 95%, and a cycle platform capacity (2nd) (<0.1V) of 180 to 228 mAh / g. Comparing the hard carbon negative electrode materials prepared from the same waste biomass (Examples 1 to 3 and Comparative Examples 1 to 3, Examples 4 to 5 and Comparative Examples 6 to 7), the battery performance of the sodium ion battery assembled with the hard carbon negative electrode prepared by organic acid pretreatment is significantly higher than that of the sodium ion battery assembled with the hard carbon negative electrode prepared without organic acid pretreatment, but the battery performance improvement effect of the sodium ion battery assembled with the hard carbon negative electrode prepared by excessively high concentration organic acid pretreatment is not as good as that of the organic acid pretreatment at a lower concentration, and the inorganic acid pretreatment (Comparative Examples 4 to 5) cannot achieve the selective removal of hemicellulose, and easily destroys the natural structure of the plant, so that the prepared hard carbon negative electrode has a lower capacity and coulombic efficiency. Therefore, the above results indicate that regulating biomass components (selectively removing and retaining cellulose and lignin) through pretreatment with organic acids at appropriate concentrations to improve electrochemical performance (capacity, first-cycle coulombic efficiency) is a general and effective means suitable for optimizing the performance of hard carbon materials prepared from different biomasses.

[0103] The first charge and discharge capacity curve of the biomass hard carbon negative electrode material for sodium ion battery prepared in Example 1 is as follows: Figure 1 As shown, it shows that the biomass hard carbon negative electrode material for sodium ion batteries has excellent cycle reversibility and high platform capacity, and the high platform capacity indicates that the material has a rich closed-pore structure for sodium storage (because the closed pores in the hard carbon are the main sodium storage sites, and the corresponding platform capacity is <0.1V; when the voltage is <0.1V, the capacity is higher, which reflects that there are more closed pores in the hard carbon). Figure 2 The charge and discharge capacity and coulomb efficiency curves of the biomass hard carbon negative electrode material for sodium ion battery prepared in Example 1 indicate that it has good cycle stability and high reversibility.

[0104] Figure 3 The XRD diagram of the biomass hard carbon negative electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 shows that the shift of the characteristic peaks in the figure indicates that the hard carbon obtained by organic acid treatment has a larger interlayer spacing. Combined with the results in Table 1, it can be seen that the increase in the interlayer spacing of the biomass hard carbon negative electrode material is beneficial to the embedding and extraction of sodium, thereby improving the capacity of the sodium ion battery prepared therefrom.

[0105] Figure 4Comparison of the charge and discharge curves of Example 1 and Comparative Examples 4 and 5 treated with inorganic acids shows that the charge and discharge capacity of the hard carbon negative electrode material treated with organic acid is higher than that of the inorganic acid. Combined with the results in Table 1, this indicates that the organic acid selectively removes the amount of hemicellulose in the plant, while the mass of cellulose and lignin remains unchanged or decreases slightly, while retaining the original three-dimensional structure of the cellulose and lignin components, achieving the construction of a microporous structure after sintering, providing more sodium storage sites and higher capacity.

[0106] In summary, the present invention uses an appropriate concentration of organic acid treatment to achieve the selective removal of hemicellulose in plants, retaining cellulose and lignin, which is beneficial to increase the interlayer spacing during high-temperature carbonization, form more micropores, and promote the improvement of electrochemical performance; compared with inorganic acid pretreatment, high-concentration organic acid pretreatment or no organic acid pretreatment, the performance of the sodium ion battery assembled with the biomass hard carbon negative electrode material prepared by organic acid pretreatment is improved, especially the initial discharge capacity and the first coulomb efficiency are significantly improved, and the specific capacity is high and the cycle stability is good. The selective regulation of hemicellulose by organic acid pretreatment with an appropriate concentration of the present invention can be used as a universal strategy for optimizing the electrochemical properties of biomass hard carbon.

[0107] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the ideas and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a biomass hard carbon negative electrode material, It is characterized in that The following steps are involved: S1. The waste biomass is crushed and sieved, pretreated with 10-50wt% organic acid solution to selectively remove hemicellulose and retain cellulose and lignin, washed and dried to obtain a biomass hard carbon precursor; S2. The biomass hard carbon precursor obtained in step S1 is pre-carbonized under an inert atmosphere to obtain a preliminary biomass hard carbon material; S3. The preliminary biomass hard carbon material obtained in step S2 is sequentially subjected to alkali treatment and acid treatment, washed to neutrality, dried, and carbonized under an inert atmosphere to obtain a sodium ion battery hard carbon negative electrode material.

2. The preparation method according to claim 1, It is characterized in that The waste biomass in step S1 is selected from one or more of fan palm, straw, and banana peel.

3. The preparation method according to claim 1, It is characterized in that The organic acid in step S1 is acetic acid, formic acid, glycolic acid or pyruvic acid.

4. The preparation method according to claim 1, It is characterized in that The pretreatment temperature of the organic acid solution in step S1 is 30-100° C., the treatment time is 0.5-5 h, and the material-liquid ratio (g / mL) of the waste biomass to the organic acid solution is 1:3-10.

5. The preparation method according to claim 1, It is characterized in that The pre-carbonization treatment in step S2 is calcination at 400-800° C. for 1-5 hours.

6. The preparation method according to claim 1, It is characterized in that In step S3, the alkali concentration in the alkali treatment is 2-15 wt %, and the alkali treatment time is 1-5 h; the acid concentration in the acid treatment is 0.5-6 mol / L, and the acid treatment time is 1-5 h.

7. The preparation method according to claim 1, It is characterized in that The carbonization treatment in step S3 is calcination at 1000-1500° C. for 1-6 hours.

8. The biomass hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the biomass hard carbon negative electrode material according to claim 8 in the preparation of sodium ion batteries.

10. A sodium ion battery comprising a negative electrode material, It is characterized in that The active material of the negative electrode material is the biomass hard carbon negative electrode material according to claim 8.

Citation Information

Patent Citations

  • Method for separation of wood fiber and homologous preparation of furfural by organic acid

    CN110684204A

  • Biomass carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass carbon negative electrode material

    CN115626630A

  • Biomass-based hard carbon material as well as preparation method and application thereof

    CN116812906A

  • Biomass hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN118173787A

  • Preparation method of hard carbon material for negative electrode of sodium ion battery and sodium ion battery

    CN118373408A

Cited By

  • Biomass-based hard carbon material, preparation method thereof and battery

    CN119735194A

  • Preparation method of cellulose-derived hard carbon negative electrode material based on ionic liquid treatment and application of cellulose-derived hard carbon negative electrode material in sodium-ion battery

    CN120004245A

  • Biomass-based hard carbon negative electrode material with high specific capacity and high magnification as well as preparation method and application of biomass-based hard carbon negative electrode material

    CN120191915A

  • A high specific capacity, high rate biomass-based hard carbon negative electrode material and a preparation method and application thereof

    CN120191915B

  • Biomass-based hard carbon material regulated and controlled by sulfonated aromatic hydrocarbon, preparation method of biomass-based hard carbon material and application of biomass-based hard carbon material in sodium-ion battery

    CN120646807A